A Critical Review on the Book Qesse-ye Solayman (An Ancient Text of Azarbaijan’s Regional Variety of Persian) - Milad Bigdeloo; Farzaneh Farahzad (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The book “Qesse-ye Solayman”, was written by Abu-Ya’qub Yusif ibn-e Ali ibn-e Omar-e Tabrizi, in the late 6th/early 7th century AH. This book has been edited critically by Alireza Imami and Ardowan Amiri-Nezhad and published by Oqāf-e Dr Afshar with Sokhan publication. The book suffers from some deficiencies with respect to textual criticism and writing. The study aimed at identifying and correcting the deficiencies of the editors’ work and correcting those items and parts overlooked by them. Also, an attempt was made to find the missing parts of the book, including the ones noticed by the editors and also the ones gone unnoticed by them. To achieve the aims of the study, other ancient Persian books were studied and compared to “Qesse-ye Solayman” and, in order to correct the deficiencies, the co-text and the context were also taken into consideration. In this study, a new word was also pinpointed in the book and its meaning was made clear by finding the word in two other books.